Media, Gender, and Identity: Challenges and Strategies for Equitable Representation - Lestari, Putri Ayu; Elfattah, Hagar Yehia Abd (Yayasan Sinergi Kawula Muda, 2025)
This narrative review explores the current state of gender representation across traditional and digital media platforms. The study aims to synthesize existing literature to understand how gender roles are portrayed, how structural systems influence representation, and what strategies can mitigate disparities. Employing a narrative method, this review analyzed peer-reviewed articles and grey literature sourced from Scopus, Web of Science, and Google Scholar, using a combination of Boolean search strategies to ensure a comprehensive dataset. Findings show that traditional media continues to depict women in stereotypical roles, while non-binary identities remain underrepresented or mischaracterized. In digital media, influencers reinforce aspirational gender norms, yet also create opportunities for visibility and activism. Intersectional research reveals that individuals with overlapping marginalized identities face compounded misrepresentation. Structural barriers—such as media ownership, editorial bias, and algorithmic filtering—sustain these portrayals. Comparative studies underscore the influence of national policy and cultural context on gender narratives. This study concludes that integrated interventions are essential to promoting authentic and diverse gender representations. Media literacy education, inclusive regulatory frameworks, and algorithmic reforms are key to disrupting entrenched inequalities. Further research should focus on longitudinal impacts and explore culturally specific media contexts to enrich global understanding.